(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2020)
The occurrence of voluntary corn has been common in Brazilian crops, due to the adoption of a succession of soybean and corn crops resistant to glyphosate. The aim of this work was to evaluate the control of voluntary corn using different doses of acetyl-CoA carboxylase (ACCase) inhibitors herbicides at different phenological stages. The experiment was carried out in a greenhouse, in a completely randomized design. The treatments were organized in a factorial scheme (3x7x2), with three herbicides (clethodim, quizalofop and clethodim + quizalofop), applied in seven doses [0; 25; 50; 100; 200; 400 and 800 mL of commercial product (C.P.) ha-1], at two phenological stages (V3 and V6). Visual control assessments were carried out at 14, 21 and 28 days after application of treatments (DAT) and shoot dry mass (SDM) at 28 DAT. The data were submitted to analysis of variance and to complementary analysis by regression adjustment. For all herbicides, the control of voluntary RR corn was greater at V3 stage, requiring lower doses compared to V6. The total control of voluntary corn plants at V3 was obtained with doses of 25 mL C.P. ha-1 for all herbicides evaluated. For V6 application, 400 mL C.P. ha-1 of clethodim and 100 mL C.P. ha-1 of quizalofop and clethodim + quizalofop were necessary to achieve 100% control. Thus, clethodim was more sensitive to advancing corn growth, compared to others herbicides, requiring higher doses to achieve complete control of volunteer corn.